2021
DOI: 10.4103/jpbs.jpbs_87_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tooth Loss Position on Oral Health-Related Quality of Life in Adults Treated in the Community

Abstract: Background: Tooth loss is known to have negative effects on both functional and psychological oral health-related quality of life (OHRQoL), but the impact of the position of the tooth loss (i.e. anterior or posterior) on the different psychosocial dimensions of OHRQoL has yet to be examined. Here, we examined how the position of lost teeth impacts the different dimensions of OHRQoL. Methods: This was a cross-sectional epidemiological study of adults age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As described by Gerritsen et al [26], this study provides clear data that tooth loss affects the severity of impairment. As described by Imam et al [27], in cases of loss of one or more teeth, the location of edentulism has some in uence on OHRQoL. Anterior tooth loss has a wide-ranging impact in physical and psychosocial terms compared with posterior tooth loss, suggesting that restoration of anterior teeth should be prioritized in treatment planning.…”
Section: Discussionmentioning
confidence: 98%
“…As described by Gerritsen et al [26], this study provides clear data that tooth loss affects the severity of impairment. As described by Imam et al [27], in cases of loss of one or more teeth, the location of edentulism has some in uence on OHRQoL. Anterior tooth loss has a wide-ranging impact in physical and psychosocial terms compared with posterior tooth loss, suggesting that restoration of anterior teeth should be prioritized in treatment planning.…”
Section: Discussionmentioning
confidence: 98%
“…When anterior teeth were lost, the participants tended to wear their upper PRDPs, which are assumed to be more noticeable, than their lower PRDPs. This highlights the impact of maxillary anterior tooth loss on psychological and social disabilities aspects [ 23 ]. Consistent with a previous study, our study reinforces the connection between PRDP usage and patients’ satisfaction with esthetics and being pain-free when using the PRDP [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible justification is that the position of missing teeth may have a greater influence on psychological factors compared with other factors. A previous study conducted among adults’ patients seeking dental treatment revealed that the location of missing teeth, especially the anterior teeth, has more negative consequences for psychosocial problems [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals who experience tooth loss and need dental treatment have a diminished quality of life as a result of compromised oral function, heightened levels of discomfort, and increased anxiety [ 12 , 13 ]. Several recognised scales, such as the Oral Health Impact Profile (OHIP) and the Geriatric Oral Health Assessment (GOHAI), may be used to evaluate dental treatment requirements [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%